2017
DOI: 10.1016/j.lindif.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive precursors of the developmental relation between lexical quality and reading comprehension in the intermediate elementary grades

Abstract: In a longitudinal study, we investigated how cognitive precursors (short-term memory, working memory, and nonverbal reasoning) influence the developmental relation between lexical quality (decoding and vocabulary) and reading comprehension skill in 282 Dutch students in the intermediate elementary grades (mean age at start Grade 4 was 9; 7 years) as these grades mark an important transition point in the development of reading comprehension skill. Analyses revealed strong autoregressive effects for the linguist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
1
10
0
4
Order By: Relevance
“…In accordance with our expectations, nonverbal reasoning contributed independently to the variance of ORC performance. This is consistent with earlier findings suggesting a supportive role for nonverbal reasoning in reading comprehension (Swart et al, 2017;Peng et al, 2018). When examining the relation of nonverbal reasoning to ORC subskills, nonverbal reasoning was found to be related to identifying main ideas and communicating.…”
Section: Nonverbal Reasoning and Prior Knowledge In Online Research Asupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with our expectations, nonverbal reasoning contributed independently to the variance of ORC performance. This is consistent with earlier findings suggesting a supportive role for nonverbal reasoning in reading comprehension (Swart et al, 2017;Peng et al, 2018). When examining the relation of nonverbal reasoning to ORC subskills, nonverbal reasoning was found to be related to identifying main ideas and communicating.…”
Section: Nonverbal Reasoning and Prior Knowledge In Online Research Asupporting
confidence: 90%
“…In addition to prior topic knowledge, theoretical models of reading specify inferential processes as integral for reading comprehension (Kendeou, McMaster, & Christ, 2016); as such, students with low verbal and nonverbal reasoning skills are more likely to have comprehension difficulties (Snowling, 2013). Nonverbal reasoning has been shown to have direct and indirect effects on reading comprehension (Swart et al, 2017); it has also been shown to support young at-risk readers' development of…”
Section: The Relation Of Prior Knowledge Reasoning and Gender To LImentioning
confidence: 99%
“…Second, early word reading and oral language skills predict concurrent and later reading comprehension (e.g., Cain, Oakhill, & Bryant, 2004; Catts et al, 2015; Dickinson & Porche, 2011; Kieffer & Vukovic, 2012), with word reading demonstrating a stronger connection to reading comprehension than to oral language, especially in the early grades (e.g., Muter et al, 2004; Roth et al, 2002; Storch &Whitehurst, 2002). A third example is that domain-general skills such as working memory and non-verbal reasoning appear directly and indirectly related to concurrent and later reading comprehension (via inferencing and vocabulary), even when other reading skills are controlled (Cain et al, 2004; Lesaux et al, 2007; Kim, 2017; Korpipää et al, 2017; Peng et al, 2018; Swart et al, 2017). Fourth, Lesaux et al (2007) reported that the development of word reading decelerates in the intermediate grades.…”
Section: Prior Research On Typically Developing Childrenmentioning
confidence: 99%
“…Sólo pudo apreciarse una correlación significativa en el grupo de niños, lo cual es consistente con los resultados obtenidos en muestras de niños con DT en las que la relación entre ambas variables está suficientemente acreditada (entre otros, Gungor, & Yayli, 2016;López-Higes, & Rubio-Valdehita, 2014;Restrepo, 2015;Swart et al, 2017).…”
Section: Discussionunclassified
“…Equivalentemente, entre los hallazgos de Oakhill y Cain (2012), en un estudio longitudinal que investigó los predictores de la comprensión lectora de niños ingleses de 7 a 8 y de 10 a 11 años, se descubrió que el vocabulario contribuía significativamente a la predicción de la capacidad de comprensión a través del tiempo. Recientemente, un estudio longitudinal, realizado con una muestra de 282 estudiantes holandeses en los grados intermedios de primaria, encon-tró evidencia de una relación recíproca entre el vocabulario y la comprensión lectora, así como la influencia de otras variables (Swart, Muijselaar, Steenbeek, Droop, De Jong, & Verhoeven, 2017).…”
unclassified